Business Student Perspectives Regarding Ways to Enhance the Online Learning Process - Kazybayeva, Aiman; Smykova , Madina; M. Krueger, Thomas; Duchshanova, Madina; Sokhatskaya , Nataliya (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The COVID-19 pandemic has highlighted the need to understand the key components of a relevant, successful online pedagogy. Using these insights, instructors in the virtual classroom can facilitate and accentuate the knowledge gained by responding to student emotional needs and perceptions. This research evaluates students’ attitudes regarding multiple facets of online instruction. In addition to revealing student opinions regarding online course characteristics, using the framework of Schmitt’s Sensory Impact Model, this report shares suggestions for improvement obtained by surveying 160 marketing and management students at a leading Central Asian university. It is the opinion of 58 percent of the students that active participation in discussions improve their academic performance. Our study further shows that astute revision of the online environment can impact student attitudes regarding online learning. Our investigation reveals that improving student motivation is a crucial step to optimizing the value added of the online knowledge transmission process. Insights to student perception regarding the importance of pedagogic factors will improve the online course as well as student perceptions of the online experience.